E-learning Based Innovation in Social Science Education - Al-Ghifari, Fauzi Tazkia (Open Access Indonesia Journal of Social Sciences, 2020)
In essence, social studies online learning innovation is an effort to meet the continuous improvement in the quality of the educational process, to meet the growing demands of society for education. Therefore, the innovation does not mean an increase in refinement and renewal of invention in the learning process that is contrary to these principles which will quickly lag and will even become an obstacle, change or delay in the innovation process. This innovation in social studies learning will be effectively carried out when indicated by the results of evaluation and research in the fieldof social studies learning. Web-based learning which is popularly known as web-based treading or sometimes called web-base d education can be defined as technology applications—web in the world of learning for an educational process. In simple terms, it can be said that all learning by utilizing internet technology, and while the learning process is felt to occur by those who follow it, this activity can be called web-based learning. Website media- based knowledge is part of the use of the internet in the world of education. It is a learning activity that utilizes website media that can be accessedvia the internet network. Website media-based learning is also a learning activity that uses media sites (websites) that can be accessed through the internet network. Website media-based learning or also known as web-based learning is one type of application of electronic learning (e -learning). Website media-based knowledge is part of the use of the internet in education and is a learning activity that utilizes website media. which can be accessed via the internet network.